Callus Formation on Endosperm from Immature and Mature Fruits of Barringtonia Racemosa - S M Soder, D; N A A Khalid, D; Saleh, A; Pardi, F; J Sidik, N (International Journal of Engineering and Technology, 2019)
Barringtonia racemosa is mangroves type of plant which had been extensively utilized in conventional practices for relieving ailments of pain and inflammation. Many studies have been done on ethnobotanical profiles, pharmacological activities and chemical compounds in Barringtonia racemosa. However, there is a limited study on callogenesis of this plant particularly from different maturity stage of fruits. The present study is to identify the callogenesis of Barringtonia racemosa from endosperm explants of immature and mature fruits in MS medium supplemented with different concentrations of hormones 2,4-Dichlorophenoxyacetic acid (2,4-D) (0, 0.5, 1.0, 1.5 and 2.0 mg/L) and Kinetin (KIN) (0, 0.5, 1.0, 1.5 and 2.0 mg/L). The optimum hormone combination was found in callus grown on endosperm of immature fruits in MS medium supplemented with 1.5 mg/L 2,4-D and 1.0 mg/L KIN. It was also found that the callus in this treatment grew profusely with highest fresh weight (0.513 Â± 0.022 g), 100% callus induction and friable callus texture. The callus fresh weight on endosperm explants was higher in immature fruits compared to mature fruits for all the hormone combinations. Therefore, callogenesis were found more efficient from endosperm explant of immature fruits in Barringtonia racemosa species.Â Â Â